2017
DOI: 10.1016/j.celrep.2017.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Stratum, a Homolog of the Human GEF Mss4, Partnered with Rab8, Controls the Basal Restriction of Basement Membrane Proteins in Epithelial Cells

Abstract: SUMMARY The basement membrane (BM), a sheet of extracellular matrix lining the basal side of epithelia is essential for epithelial cell function and integrity. Yet, the mechanisms that control the basal restriction of BM proteins are poorly understood. In epithelial cells, a specialized pathway is dedicated to restrict the deposition of BM proteins basally. Here we report the identification of a factor in this pathway, a homolog of the mammalian guanine nucleotide exchange factor (GEF) Mss4, that we named Stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 31 publications
10
33
0
Order By: Relevance
“…We found that AP-1 and Strat act redundantly to control the basolateral targeting of Notch, Delta and Spdo in SOP daughter cells explaining the partial compensation of one by the other. These results are in agreement with previous studies demonstrating the involvement of Rab8, whose activity and localization is controlled by Strat in Drosophila (Bellec et al, 2018;Devergne et al, 2017), in the basolateral sorting of proteins (Ang et al, 2003;Henry and Sheff, 2008;Huber et al, 1993).…”
Section: Strat and Ap-1 Act Redundantly In The Basolateral Transport supporting
confidence: 94%
“…We found that AP-1 and Strat act redundantly to control the basolateral targeting of Notch, Delta and Spdo in SOP daughter cells explaining the partial compensation of one by the other. These results are in agreement with previous studies demonstrating the involvement of Rab8, whose activity and localization is controlled by Strat in Drosophila (Bellec et al, 2018;Devergne et al, 2017), in the basolateral sorting of proteins (Ang et al, 2003;Henry and Sheff, 2008;Huber et al, 1993).…”
Section: Strat and Ap-1 Act Redundantly In The Basolateral Transport supporting
confidence: 94%
“…We then wondered whether BM fibril deposition is affected in Dys and Dg mutants. In these two mutants, the general targeting of BM secretion towards the basal domain is normal, with no visible apical secretion as it has been observed in different mutants affecting BM secretion (Denef et al, 2008;Devergne et al, 2014;Lerner et al, 2013;Devergne et al, 2017). However, images in the focal plane of the BM reveal a very strong decrease of the ColIV-fibrils in Dys null mutant ( Fig.…”
Section: The Dapc Is Important For Bm Fibril Depositionsupporting
confidence: 56%
“…Chemical inhibition or genetic ablation of Pten in Crb-deficient glands not only suppresses the formation of PAMS, but also restores the apical pools of Rab11, Rab30, apical secretion, larval food intake and timely pupariation. The relevance of PI(4,5)P 2 levels for proper secretion is highlighted by recent results demonstrating that the activity of Drosophila Crag (a Rab10 GEF) and Stratum (a Rab8 GEF) is regulated by the levels of PI(4,5)P 2 (Devergne et al, 2014; 2017). For example, in the follicle epithelium, reduction of PI(4,5)P 2 levels results in defective secretion of basal membrane proteins, which then accumulate at the apical membrane (Devergne et al, 2014; 2017).…”
Section: Discussionmentioning
confidence: 99%